Management of the osteoarthritic and rheumatoid wrist. Issue 4 (August 2021) - Stevens, Richard; Storey, Phil
Abstract: Arthritis of the wrist has multiple causes, with post-traumatic being the most common non-inflammatory cause, and rheumatoid arthritis the most common inflammatory condition. Management starts with detailed history, examination and functional assessment. Surgical options include wrist denervation, correction of carpal deformities (distal radius osteotomy, ligament tenodesis), excision of the affected articulations (scaphoidectomy, styloidectomy, proximal row carpectomy), arthrodesis (four corner fusion, limited carpal fusions, total wrist arthrodesis) and total wrist arthroplasty. Similar procedures can be performed at the distal radioulnar joint. This article reviews the causes of wrist arthritis and evidence behind the management options.